Pemanfaatan Limbah Botol Pelastik untuk Meningkatkan Kreatifitas Anak melalui Pelatihan Pengolahan Sampah Botol Plastik menjadi Tempat Pensil - Wardatun Nisa Sipahutar; Harahap, Aisyah Amalia; Melati Sucila; Jumiati (PAKAT: Jurnal Pengabdian Kepada Masyarakat, 2025)
The use of disposable plastic bottles in mineral water, coffee, soda and other beverage products continues to increase every year. The increase in the use of disposable plastic bottles contributes to a significant increase in the amount of plastic waste. This can have a negative impact and damage the environment. Many studies have been conducted by developed countries that one of the ways that is often done to overcome plastic waste is to carry out the 3R process, namely Reuse, Reduce, Recycle. For example, it is reprocessed into plastic pellets. The plastic bottle waste processing method is used for PKM training activities. This training aims to instill a sense of concern for the environment in children as early as possible. The next goal is to increase children's creativity in processing plastic bottle waste that can no longer be used and then processed into something valuable. The subjects selected for this activity were children at elementary school level located in the Pintu Padang II sub-district. The training was carried out at the post with a target of 20 students. The benefits obtained from this training are that students have increased creativity in processing plastic waste into handicrafts, and increase children's concern for the environment.